Analisis Aspek Lingkungan Kerja Dan Beban Kerja Terhadap Kinerja Karyawan - Putri Sri Lestari; Yunita Puspita Kencana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to analyze aspects of the work environment and workload on employee performance. The method used in this research is descriptive qualitative. The data collection technique used in this research is interviews. The results of the research and discussion show that the work environment has a positive effect on employee performance. This means that if the conditions of a good work environment can increase work comfort in doing their work, if employees carry out their duties optimally, the quality of employee performance will increase. Workload has a negative effect on employee performance. This means that the higher the workload without any division of tasks to other employees, the employee's performance will decrease. Too heavy or too light workload affects work efficiency, too little workload causes companies to pay more employees for the same productivity. The work environment and workload have a significant effect on employee performance. This means that the work environment and workload are said to be good if employees perform optimally. The creation of a good working environment and workload will determine success in achieving company goals.